Mainshock-aftershock damage assessment of infilled RC structures - Furtado, André (2019)
The primary objective of this manuscript is to present a numerical study regarding the mainshock-aftershock damage assessment of infilled reinforced concrete (RC) structures. For this, an 8 storey building was built in the OpenSees software considering different modelling strategies: (i) RC structure without infill masonry walls; (ii) RC structure with infill walls considering only the in-plane behaviour; and (iii) RC structure with infill walls considering the combined in-plane and out-of-plane non-linear behaviour. Two different approaches are proposed to assess the seismic vulnerability of undamaged and damaged structures due to mainshock-aftershock sequences. Both methodologies are described throughout the manuscript. Incremental dynamic analysis were carried out to achieve fragility curves for different damage states of the structures. A comparison between the undamaged and damaged structures’ fragility curves will be presented and discussed which will allow to assess the effect of the mainshock-aftershock. Furthermore, the effect of the infill walls presence and the consideration of the combined in -plane and out-of-plane behaviour will be discussed.